2022
DOI: 10.1590/s1677-5538.ibju.2021.0457
|View full text |Cite
|
Sign up to set email alerts
|

Should obesity be associated with worse urinary continence outcomes after robotic-assisted radical prostatectomy? a propensity score matching analysis

Abstract: Purpose:To analyze the association between obesity and urinary incontinence rate in men submitted to robot-assisted radical prostatectomy (RARP) in a high-volume cancer center. Materials and Methods: We reported 1.077 men who underwent RARP as the primary treatment for localized prostate cancer from 2013 to 2017. Patients were classifi ed as non-obese (normal BMI or overweight) or obese men (BMI ≥30kg/m 2 ). They were grouped according to the age, PSA level, D'Amico risk group, Gleason score, ASA classifi cati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 23 publications
0
5
0
1
Order By: Relevance
“…Finally, the results found in this study must be evaluated with caution regarding biases when comparing continence rates after LRP before and after 2011, especially if one is inclined to compare them to open radical prostatectomy and robotic-assisted radical prostatectomy (RALP) rates. This novel methodology of RSR also allows for PPI measurement criteria and their rates to be compared in future studies, including RALP, which is the main RP technique currently (16)(17)(18). Its strength is beyond scientometrics, adding to the evidence-based medicine by temporally analyzing the surgical complication in question, allowing possible projections for the future, and exposing significant bias neglected by SRs.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the results found in this study must be evaluated with caution regarding biases when comparing continence rates after LRP before and after 2011, especially if one is inclined to compare them to open radical prostatectomy and robotic-assisted radical prostatectomy (RALP) rates. This novel methodology of RSR also allows for PPI measurement criteria and their rates to be compared in future studies, including RALP, which is the main RP technique currently (16)(17)(18). Its strength is beyond scientometrics, adding to the evidence-based medicine by temporally analyzing the surgical complication in question, allowing possible projections for the future, and exposing significant bias neglected by SRs.…”
Section: Discussionmentioning
confidence: 99%
“…We did not identify any influence of BMI or prostate volume on postoperative urinary continence. Although previous studies reported that a lower BMI and smaller prostate volume were associated with the better recovery of urinary continence ( 11 , 12 ), these findings are controversial in terms of the relationship between obesity and urinary incontinence after RP ( 28 ). Another study showed that the influence of prostate volume on continence varied ( 29 ).…”
Section: Discussionmentioning
confidence: 98%
“…First, there is a certain heterogeneity among studies mainly caused by the diversity of PFME schemes in the studies. Other factors included the differences of definition of UI, the intensity and frequency of interventions, and surgical procedures ( 32 , 33 ). In addition, the included studies could not blind the experimenters and the interveners in this study with PICO, which may affect the results.…”
Section: Discussionmentioning
confidence: 99%